Fipronil Triggers Immunotoxicity Through Reactive Oxygen Species-Driven Mitochondrial Apoptosis in Thymocytes - Jui-Fang Kuo; Yai-Ping Hsiao; Yao-De Wang; Hsin-Pei Weng; Chia-Chi Wang (Toxics)
Fipronil (FPN), a widely used pesticide, is associated with significant immunotoxic effects, particularly impacting thymocyte survival and immune homeostasis. This study explores the mechanistic pathways underlying FPN-induced apoptosis and oxidative stress. Short-term FPN exposure (1–10 mg/kg) notably suppressed the expression of both anti-apoptotic (Bcl-2, Bcl-6, Mcl-1) and pro-apoptotic (Bnip3, Bim) genes in thymic tissues in vivo. Additionally, in isolated primary thymocytes, FPN directly decreased the expression of Bcl-2, Bcl-6, Mcl-1, and Bnip3 expression, coupled with a significant increase in pro-apoptotic Bim expression in a dose-dependent manner. FPN treatment directly led to elevated reactive oxygen species (ROS), lipid peroxidation, mitochondrial membrane depolarization, reduced cellular metabolic activity, and depleted intracellular calcium and glutathione (GSH) levels, indicating mitochondrial dysfunction and oxidative stress. Annexin V/PI staining confirmed that FPN induced late-stage apoptosis and necrosis in primary thymocytes. These findings elucidate the immunotoxic effects of FPN on thymocytes, highlighting its detrimental impact on immune system integrity, thymic development, and T cell maturation through oxidative damage and mitochondrial-mediated apoptosis.